Characterization of I-Ppo, an intron-encoded endonuclease that mediates homing of a group I intron in the ribosomal DNA of Physarum polycephalum. - Muscarella, D E (1990)
A novel and only recently recognized class of enzymes is composed of the site-specific endonucleases encoded by some group I introns. We have characterized several aspects of I-Ppo, the endonuclease that mediates the mobility of intron 3 in the ribosomal DNA of Physarum polycephalum. This intron is unique among mobile group I introns in that it is located in nuclear DNA. We found that I-Ppo is encoded by an open reading frame in the 5' half of intron 3, upstream of the sequences required for self-splicing of group I introns. Either of two AUG initiation codons could start this reading frame, one near the beginning of the intron and the other in the upstream exon, leading to predicted polypeptides of 138 and 160 amino acid residues. The longer polypeptide was the major form translated in vitro in a reticulocyte extract. From nuclease assays of proteins synthesized in vitro with partially deleted DNAs, we conclude that both polypeptides possess endonuclease activity. We also have expressed I-Ppo in Escherichia coli, using a bacteriophage T7 RNA polymerase expression system. The longer polypeptide also was the predominant form made in this system. It showed enzymatic activity in bacteria in vivo, as demonstrated by the cleavage of a plasmid carrying the target site. Like several other intron-encoded endonucleases, I-Ppo makes a four-base staggered cut in its ribosomal DNA target sequence, very near the site where intron 3 becomes integrated in crosses of intron 3-containing and intron 3-lacking Physarum strains.